Investigation of risk of dementia diagnosis and death in patients in older people's secondary care mental health services. (4th November 2020) - Kershenbaum, Anne; Cardinal, Rudolf N.; Chen, Shanquan; Underwood, Benjamin R.; Seyedsalehi, Aida; Lewis, Jonathan; Rubinsztein, Judy Sasha
Abstract: Objectives: Previous studies have shown increased rates of death and dementia in older people in specific serious mental illnesses (SMI) such as bipolar disorder or depression. We examined the rates of death and dementia in older people referred into a secondary care psychiatric service across a range of SMIs. Methods: We used an anonymised dataset across 6 consecutive years with 28, 340 patients aged 65 years and older from a single secondary care psychiatric trust in the United Kingdom. We identified deaths and incident dementia in patients with bipolar disorder/mania, schizophrenia, recurrent depression and anxiety disorders. We compared mortality and dementia rates between these diagnostic groups and in different treatment settings. We also examined mortality rates and dementia rates compared with general population rates. Results: Patients with schizophrenia showed the highest hazard rate for death compared to other groups with SMIs (hazard ratio, 1.58; 95% confidence interval (CI), 1.18–2.1, with anxiety group the reference). Survival was reduced in patients referred to liaison psychiatry services. There were no significant differences between the SMI groups in terms of rates of dementia. However, risks of death and dementia were significantly increased compared to the general population (standardized mortality rates with 95% CI, 2.6(2.0–3.3), 3.5(2.6–4.5), 2.5(2.0–3.0) and 1.8 (1.4–2.2) and standardized dementia incidence rates with 95% CI, 2.7(1.5–4.1), 2.9(1.5–4.7), 3.8(2.6–5.2) and 4.3 (3.0–5.7) for bipolar disorder/mania, schizophrenia, recurrent depression and anxiety disorders respectively. Conclusions: Older adults referred into an old age psychiatry service show higher rates of dementia and death than those reported for the general population.